2017
DOI: 10.1177/1362168817722054
|View full text |Cite
|
Sign up to set email alerts
|

On self-reported use of communication strategies by CLIL learners in primary education

Abstract: The use of communication strategies (CSs) in oral and written second language (L2) production has been widely investigated (e.g. Muñoz, 2007). As for content and language integrated learning (CLIL) settings, learners seem to resort to the first language (L1) less often than in traditional foreign language instruction (e.g. Celaya & Ruiz de Zarobe, 2010). However, few studies have examined what L2 learners say about their use of CSs by means of questionnaires-e.g. Ehrman & Oxford (1990), with adult English as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 37 publications
(72 reference statements)
0
10
0
2
Order By: Relevance
“…No differences between the two age/proficiency groups were observed. As for the distribution of categories, holistic strategies were the most employed, a finding attributed to the overriding effect of CLIL as reported in other investigations with young learners that have analysed self--reported opinions (Martínez--Adrián, Gallardo--del--Puerto, & Basterrechea, 2019). In other words, even if these participants were considered low--proficient learners, they were exploiting strategies more typical of advanced learners, a result that might be due to the type of input received in their CLIL lessons, which is full of reformulations in the TL.…”
Section: Research In Clil Settingsmentioning
confidence: 65%
“…No differences between the two age/proficiency groups were observed. As for the distribution of categories, holistic strategies were the most employed, a finding attributed to the overriding effect of CLIL as reported in other investigations with young learners that have analysed self--reported opinions (Martínez--Adrián, Gallardo--del--Puerto, & Basterrechea, 2019). In other words, even if these participants were considered low--proficient learners, they were exploiting strategies more typical of advanced learners, a result that might be due to the type of input received in their CLIL lessons, which is full of reformulations in the TL.…”
Section: Research In Clil Settingsmentioning
confidence: 65%
“…These learners were primarily making use of appeals for assistance during vocabulary deliberations, which they were producing entirely in Spanish most of the time. Appeals for assistance are strategies widely used by young learners in recent investigations carried out with children and oral production (Azkarai & García Mayo, 2017;García Mayo & Hidalgo, 2017;Martínez-Adrián, 2020a), and also with children and self-reported opinions (Martínez-Adrián, Gallardo-del-Puerto, & Basterrechea, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The instructional functions of the teachers' speech acts were to control the children's behaviors, to organize learning situations, and to motivate children for learning. Besides, (Martínez-Adrián et al,2017) conducted a study on self-reported use of communication strategies by content and language integrated learning (CLIL) in primary education. Learners' self-reported opinions about the use of communication strategies (guessing, miming, morphological creativity, dictionary, predicting, paraphrasing, borrowing, calque, foreignizing, avoidance and appeal for assistance) were being examined to collect the data needed.…”
Section: Introductionmentioning
confidence: 99%